A Kinetic Approach for Employing Two Duckweed Species, Lemna minor, and Spirodela polyrhiza, in the Sustainable Aquaculture Wastewater Treatment and Fish Feed Production - Rifai, Ridwan Muhamad; Yulistyorini, Anie; Siswahyudi, Dwi; Pratiwi, Jenvia Rista; Fauzi, Ichsan Achmad; Rachminiwati, Nina (HAYATI Journal of Biosciences, 2024)
Duckweed, a widely used natural fish feed, has also become more popular as the phytoremediation agent for wastewater, including one sourced from aquaculture. These two features indicate that duckweed can be utilized in a sustainable aquaculture system by treating and reclaiming nutrients from wastewater and then harvesting them for fish feed production. Hence, this study attempted to assess the approach of the two most known duckweed species, i.e., Lemna minor and Spirodela polyrhiza, in depleting NH4 and PO4 from synthetic controlled aquaculture wastewater as well as to understand their yield based on the N : P ratio. Cultivation in synthetic aquaculture wastewater media was carried out, followed by nutrient uptake and growth analysis. According to statistical analysis, both L. minor and S. polyrhiza could remove NH4 and PO4 with a relatively equal rate (p-val > 0.050). Nonetheless, both duckweed species absorb nitrogen more easily than phosphorous (p-val < 0.050). Considering the yield based on nutrient uptake, NH4 drove a more efficient yield for L. minor to S. polyrhiza at 16.70 g dry biomass/g NH4 and 14.14 g dry biomass/g NH4, respectively. Meanwhile, a higher yield was observed on S. polyrhiza than on L. minor regarding PO4 concentration, at 19.31 g dry biomass/g PO4 and 9.10 g dry biomass/g PO4, respectively. Therefore, a strategy to remove nutrients and produce biomass for fish feed can be formulated based on the N : P concentration ratio, where L. minor tends to produce biomass more rapidly in a higher N : P ratio, whereas S. polyrhiza works in the opposite.